Single-Nanofiller Modification of Epoxy Adhesives for Bonded GFRP Composite Joints: A Strengthened Static Screening Study - Ahmed Ahmed, Bilal Faaek; Sulukan, Egemen; Erklig, Ahmet (Journal of Research Updates in Polymer Science, 2026)
The use of epoxy adhesives has grown rapidly in polymer-composite assemblies because they can transfer load across a continuous bonded area and do not require drilling or fibre interruption. The static reliability of epoxy-bonded glass-fibre-reinforced polymer (GFRP) joints, however, could be limited by the brittleness of the cured network, and the issues of bond-line defects and the selection of an appropriate single-nanofiller modifier. This work is a statistically validated screening of single nanofiller epoxy adhesives of bonded GFRP composite joints. From the broader experimental results, six different adhesive systems were chosen: neat epoxy (F14), 0.3 wt% multi-walled carbon nanotube (MWCNT)/epoxy (F6), 1 wt% graphene nanoplatelet (GNP)/epoxy (F7), 0.5 wt% silica/epoxy (F9), 0.5 wt% clay/epoxy (F11) and 0.3 wt% boron nitride (BN)/epoxy (F13). The following performance measures were used in this evaluation of the selected systems: peak tensile load in single lap-joint loading, flexural strength in three-point bending, dispersion measures, 95% confidence intervals, Welch ANOVA, Games-Howell comparisons, normalized cross-loading performance, and macroscopic failure evidence. The MWCNT/epoxy formulation exhibited the highest mean peak tensile load being 123.1% higher than neat epoxy. The highest mean flexural strength (67.50 MPa) was recorded for MWCNT/epoxy and GNP/epoxy, which were 328.6% higher than neat epoxy. Moderate improvements were observed with silica and clay while BN at the loading tested was limited in mechanical improvement. Structural qualification considerations of repeatability, dispersion control and evidence of failure make these findings practically significant because carbon single-nanofiller systems, specifically MWCNT and GNP are identified as the most promising baseline modifiers to improve the static capacity of epoxy-bonded GFRP joints.